KEANEKARAGAMAN MANGROVE DI DESA GEDANGAN, KECAMATAN PURWODADI, KABUPATEN PURWOREJO, JAWA TENGAH - Slamet Mardiyanto Rahayu; Syuhriatin Syuhriatin; Wiryanto Wiryanto (Universitas Lambung Mangkurat, 2018)
This research aims to know the diversity of mangrove in Gedangan Village, Purwodadi Subdistrict, Purworejo Regency, Central Java. This research conducted on June-September 2016 with purposive sampling methods with three station. Based on the results of the research are nine mangrove species found are rhizophora mucronata, sonneratia alba, nypa fruticans, hibiscus tiliaceus, ipomoea pescaprae, acanthus ilicifolius, gymnanthera paludosa, wedelia biflora, and scirpus sp. Diversity of tree mangrove are low (H’ station 2=0,95 and H’ station 3= 0,15). Diversity of sapling mangrove are low with H’ in station 1, 2, and 3 are 0,2; 0,68; dan 0,08. And the diversity of mangrove seedling and lower plants are medium with H’ in station 1, 2, and 3 are 1,17; 1,56; and 1,48. Environment condition in all station is relatively good to support the life of mangrove plant. That is temperature 28-30 0C; pH 7-8; DO 4,0-6,5 mg/l; salinity 6-9 ppt; and sandy mud substrate.